Intervertebral Disc Swelling Demonstrated by 3D and Water Content Magnetic Resonance Analyses after a 3-Day Dry Immersion Simulating Microgravity - Treffel, Loïc; Mkhitaryan, Karen; Gellee, Stéphane; Gauquelin-Koch, Guillemette; Gharib, Claude; Blanc, Stéphane; Millet, Catherine (Frontiers in Physiology, 2016)
Background Vertebral deconditioning is commonly experienced after space flight and simulation studies. Disc herniation (DH) is quadrupled after space flight. Purpose The main hypothesis formulated by the authors is that microgravity results in intervertebral disc swelling. Study Design The aim of the study was to identify the morphological changes of the spine and their clinical consequences after simulated microgravity by 3-day dry immersion (DI). The experimental protocol was performed on 12 male volunteers using magnetic resonance imaging and spectroscopy before and after DI. Methods All the experiment was financially supported by CNES (Centre national d’études spatiales i.e. French Space Agency). Results We observed an increase in rachis height of 1.5 ± 0.4 cm and a decrease in curvature, particularly for the lumbar region with a decrease of -4 ± 2.5°. We found a significant increase in intervertebral disc (IVD) volume of +8 ± 9% at T12-L1 and +11 ± 9% at L5-S1. This phenomenon is likely associated with the increase in disc intervertebral water content (IWC), 17 ± 27%. During the 3 days in DI, 92% of the subjects developed back pain in the lumbar region below the diaphragmatic muscle. This clinical observation may be linked to the morphological changes of the spine. Conclusions The morphological changes observed and, specifically, the disc swelling caused by increased IWC may contribute to understanding disc herniation after microgravity exposure. Our results confirmed the efficiency of the 3-day DI model to reproduce quickly the effects of microgravity on spine morphology. Our findings raise the question of the subject selection in spatial studies, especially studies about spine morphology and reconditioning programs after space flight. These results may contribute to a better understanding of the mechanisms underlying disc herniation and may serve as the basis to develop countermeasures for astronauts and to prevent IVD herniation and back pain on Earth.